An Analysis of The Effect of Organizational Climate, Compensation, and Leadership Style on Employee Performance at Pelni Hospital Jakarta - Amy Devriady; Syauzul Wisda Pradipta; Tri Prasetyo; Chotamul Fajri (Peneliti.net, 2022)
This study aims to determine how the influence of organizational climate, compensation, and leadership style on employee performance at PELNI Hospital Jakarta. The research method used in this research is descriptive research method with a quantitative approach. The population of this research is 1,428 employees of PELNI Hospital Jakarta, with the sample studied is 312 employees. The research hypothesis was tested using the Structural Equation Model (SEM) approach using SmartPLS (Partial Least Square) 3.0. The results showed that organizational climate, compensation, and leadership style, either partially or simultaneously, had a positive and significant effect on employee performance. This means that, among the ways for PELNI Hospital management to be able to further improve the performance of its employees, namely by creating and maintaining a conducive organizational climate, providing better compensation, and implementing a more mature leadership style.